2017
DOI: 10.17221/111/2016-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness and innovation of the Polish food industry

Abstract: Agribusiness is the biggest production sector in the European Union taking into account both the value of turnover and the creation of added value as well as employment size. In this context, the food industry deserves a special distinction. In the publication, the analyses of the food industry competitiveness in Poland are presented. For analysing and assessing competitiveness of the Polish food industry, the following factors were used: the orientation of export (OE), covering of import by export (TC), the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Hungary and Poland represent competitive markets, according to this study. Strong position in agri-food competitiveness of Poland compared to other Central European countries was identified also by other authors (Poczta and Pawlak, 2011;Firlej et al, 2017).…”
Section: /474supporting
confidence: 73%
“…Hungary and Poland represent competitive markets, according to this study. Strong position in agri-food competitiveness of Poland compared to other Central European countries was identified also by other authors (Poczta and Pawlak, 2011;Firlej et al, 2017).…”
Section: /474supporting
confidence: 73%
“…Wijnands, Van Berkum, and Verhoog (2015) concluded that gaining a competitive advantage is the key to success. According to Firlej, Kowalska, and Piwowar (2017) adopting and implementing innovations, having a favorable trade balance, and exporting are all important aspects of gaining a competitive edge in the Polish food business. Moreover, the role of innovation was also studied on the point of consumer innovativeness at this time by Sulkowski (2017), who concluded that consumer innovativeness is a basic source for the creation of competitive advantage of firms.…”
Section: τHe Notion Of Competitionmentioning
confidence: 99%
“…In the food industry, investments and innovations basis for competitiveness companies (Firlej et al, 2017). However, new technologies, which affect all areas of activity, are only a means of achieving sustainable business growth.…”
Section: Introductionmentioning
confidence: 99%